Early rehabilitation in critical care (eRiCC): functional electrical stimulation with cycling protocol for a randomised controlled trial. Issue 5 (13th September 2012) - Parry, Selina M; Berney, Sue; Koopman, René; Bryant, Adam; El-Ansary, Doa; Puthucheary, Zudin; Hart, Nicholas; Warrillow, Stephen; Denehy, Linda
Abstract : Introduction: Intensive care-acquired weakness is a common problem, leads to significant impairment in physical functioning and muscle strength, and is prevalent in individuals with sepsis. Early rehabilitation has been shown to be safe and feasible; however, commencement is often delayed due to a patient's inability to co-operate. An intervention that begins early in an intensive care unit (ICU) admission without the need for patient volition may be beneficial in attenuating muscle wasting. The eRiCC (early rehabilitation in critical care) trial will investigate the effectiveness of functional electrical stimulation-assisted cycling and cycling alone, compared to standard care, in individuals with sepsis. Methods and analysis: This is a single centre randomised controlled trial. Participants (n=80) aged ≥18 years, with a diagnosis of sepsis or severe sepsis, who are expected to be mechanically ventilated for ≥48 h and remain in the intensive care ≥4 days will be randomised within 72 h of admission to (1) standard care or (2) intervention where participants will receive functional electrical muscle stimulation-assisted supine cycling on one leg while the other leg undergoes cycling alone. Primary outcome measures include: muscle mass (quadriceps ultrasonography; bioelectrical impedance spectroscopy); muscle strength (Medical Research Council Scale; hand-held dynamometry) and physical function (Physical Function in Intensive Care Test; Functional Status Score in intensive care; 6 min walk test). Blinded outcome assessors will assess measures at baseline, weekly, at ICU discharge and acute hospital discharge. Secondary measures will be evaluated in a nested subgroup (n=20) and will consist of biochemical/histological analyses of collected muscle, urine and blood samples at baseline and at ICU discharge. Ethics and dissemination: Ethics approval has been obtained from the relevant institution, and results will be published to inform clinical practice in the care of patients with sepsis to optimise rehabilitation and physical function outcomes. Trial registration: Australian and New Zealand Clinical Trials Registry ACTRN12612000528853.